The Pledges as Alternative to Witnesses in Waqf and Grant Transactions: A Comparative Study of Fiqh Madhhabs - Maulidah, Tahani Asri; Hasan, Nugraha; Nurjannah (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aimed to analyze the role of witnesses and pledges in the settlement of waqf and grant disputes based on the perspective of Islamic law. Although Islamic law had regulated these two concepts in detail, there remained uncertainty in the application regarding the validity of witnesses and pledges in waqf and grant transactions. This analysis focused on addressing the effectiveness of the two concepts in resolving conflicts. A qualitative method with a normative approach was adopted, which further depended on literature studies and juridical analysis of classical and contemporary Islamic legal texts. Data were collected through a review of the fiqh madhhabs legal literature as well as relevant fatwas and further analyzed using the descriptive-analytical method. The results showed that witnesses and pledges played a significant role in determining the validity of waqf and grant transactions. In particular, the pledges could be used as evidence when witnesses were unavailable or ineligible. However, applying both concepts required adjustments to the local context and community customs. The originality of this study lay in the comprehensive approach to the pledges as a legitimate alternative in dispute resolution, providing a new solution in the context of modern Islamic law. Furthermore, this study provided an important contribution to the development of Islamic law related to waqf and grant transactions. The implications of this study were the need for more adaptation to local conditions and further exploration of the practical implementation of these elements.